A Global Data Analysis for Representing Sediment and Particulate Organic Carbon Yield in Earth System Models. Issue 12 (21st December 2017) - Tan, Zeli; Leung, L. Ruby; Li, Hongyi; Tesfa, Teklu; Vanmaercke, Matthias; Poesen, Jean; Zhang, Xuesong; Lu, Hui; Hartmann, Jens
Abstract: Although sediment yield (SY) from water erosion is ubiquitous and its environmental consequences are well recognized, its impacts on the global carbon cycle remain largely uncertain. This knowledge gap is partly due to the lack of soil erosion modeling in Earth System Models (ESMs), which are important tools used to understand the global carbon cycle and explore its changes. This study analyzed sediment and particulate organic carbon yield (CY) data from 1, 081 and 38 small catchments (0.1–200 km 2 ), respectively, in different environments across the globe. Using multiple statistical analysis techniques, we explored environmental factors and hydrological processes important for SY and CY modeling in ESMs. Our results show clear correlations of high SY with traditional agriculture, seismicity and heavy storms, as well as strong correlations between SY and annual peak runoff. These highlight the potential limitation of SY models that represent only interrill and rill erosion because shallow overland flow and rill flow have limited transport capacity due to their hydraulic geometry to produce high SY. Further, our results suggest that SY modeling in ESMs should be implemented at the event scale to produce the catastrophic mass transport during episodic events. Several environmental factors such as seismicity and land management that are often not considered in current catchment‐scale SY models can be important in controlling global SY. Our analyses show that SY is likely the primary control on CY in small catchments and a statistically significant empirical relationship is established to calculate SY and CY jointly in ESMs. Plain Language Summary: Sediment and organic carbon in the rivers produced by soil erosion are ubiquitous. Although they have important effects on the global carbon cycle, current models have limitations in representing sediment and particulate organic carbon (POC) yield at temporal and spatial scales relevant to Earth System Models (ESMs). By analyzing the sediment yield data from over 1000 small catchments across the globe, we identified environmental factors and hydrological processes important for modeling sediment yield in ESMs. Based on the POC yield data, we indicated that sediment yield is likely the primary control on POC yield. Importantly, we also established a statistical significant empirical relationship relating POC yield to sediment yield that can be used in ESMs. Key Points: SY should be modeled in ESMs at the event scale with including erosion processes more than interrill and rill erosion Seismicity and land management that are rarely considered in current models could be important for controlling global SY A statistically significant empirical relationship between sediment and POC yield has been established for simulating them jointly in ESMs